Peningkatan Kompetensi Guru Dalam Merancang Modul Praktikum Jurusan Caregiver SMK Mandala Bhakti Surakarta - Rahmasari, Ikrima; Wahyudi, Totok; Purwaningsih, Iswanti (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Vocational education (SMK) has an important role in preparing and equipping students with scientific and technological abilities as well as vocational skills for professions in accordance with society's needs. This means that every educational unit is required to have facilities, especially for practicum learning, which requires learning media such as modules to support an orderly and sustainable learning process. Learning modules are very necessary for practical learning to train students' independence to actively think critically during the teaching and learning process. The aim of this service is to assist the driving teacher in creating a practicum module for the cargiver department. The targets for the community service carried out were 8 teachers at Mandala Bhakti Vocational School, Surakarta, majoring in Caregiver. The method used is to provide material about making practicum modules and assistance in making practicum modules. The overall results achieved by the implementation of the activities have gone well and received a positive or very satisfactory response from the participants (indicated by an average score above 3.5. Overall, the series of activities was viewed positively by the activity participants as evidenced by the formation of a practicum module draft in accordance with with each teacher's field.